Rekonstruksi Tata Kelola Maritim dan Kelestarian Religi: Strategi Pengentasan Kemiskinan Berbasis Masyarakat Hukum Adat di Situs Maudori, Kabupaten Supiori - Ngilamele, Rafles; Suhartono, Tony; Suryady, Robertus (JURNAL TABGHA, 2026)
Background: Supiori Regency, Papua, records an extreme poverty rate of 42.6% (2025) a paradox given its rich marine resources and historical-religious significance as the site of the first Gospel landing (1908). Technocratic development approaches have failed to address structural poverty by overlooking indigenous knowledge systems and institutional structures. Methods: This study employs a qualitative approach with an instrumental case study design. Data were collected through a Focus Group Discussion (FGD) minutes on the identification and mapping of the Indigenous Law Community (MHA) of West Supiori District (March 2026), in-depth interviews with key informants, participatory observation at the "Maudori for All" proclamation (February 2026), and document analysis. Data analysis followed the Miles, Huberman, and Saldaña model with source and method triangulation. Results: The study identified an active hierarchical indigenous institutional structure (Sup Mnuk Wabu–Mananwir) across five villages, the sasisen practice as a form of traditional Territorial Use Rights in Fisheries (TURFs), and rich cultural-religious assets yet to be sovereignly monetised. The proclamation of "Maudori for All" with 8 Prayer Points of Restoration demonstrates strategic integration of spiritual values into public policy. Conclusion: Poverty alleviation in Supiori requires three simultaneous pillars: legal recognition of maritime customary rights through indigenous peoples' legislation (Perda MHA); strengthened collaborative governance based on the Three Hearthstones model (government–customary–church); and community-based economic development positioning indigenous communities as owners, not objects, of development.